Remote sensing to quantify in-field soil moisture variability in irrigated maize production - Siegfried, Jeffrey Alan, author; Khosla, Raj, advisor; Longchamps, Louis, committee member; Wallner, Barbara, committee member (Colorado State University. Libraries, 2016)
Agriculture is the largest consumer of water globally. As pressure on available water resources increases, the need to exploit technology in order to produce more food with less water becomes crucial. The technological hardware requisite for precise water delivery methods such as variable rate irrigation is commercially available. Despite that, techniques to formulate a timely, accurate prescription for those systems are inadequate. Spectral vegetation indices, especially Normalized Difference Vegetation Index, are often used to gauge crop vigor and related parameters (e.g. leaf nitrogen content and grain yield). However, research heretofore rarely addresses the influence of soil moisture on the indices. Canopy temperature measured using inexpensive infrared thermometers could also serve as an indicator of water stress, but current methods which exploit the data can be cumbersome. Therefore, the objectives of this study were to determine 1) if vegetation indices derived from multispectral satellite imagery could assist in quantifying soil moisture variability in an irrigated maize production system 2) the period of time which a single image is representative of soil moisture conditions 3) to determine the relationship between synchronous measurements of crop canopy temperature and in-field soil moisture tension, and 4) to understand the influence of discretionary crop canopy temperature stress thresholds on the relationship between soil moisture tension and crop canopy temperature. A variable rate irrigation pivot was used to form six water treatment zones. Each zone was equipped with both a set of tensiometers installed in the center of the plots at 20, 45, and 75cm depths and an infrared thermometer pointed into the crop canopy to individually monitor conditions in the water treatment zones. Water was applied for each treatment as a percentage of the estimated evapotranspiration (ET) requirement: i.e., 40, 60, 80, 100, 120, and 140 percent of the ET. Data collected from tensiometers was paired with the image pixels corresponding to the ground location of the tensiometers and with the synchronous canopy temperature data. Statistical analysis was performed separately to assess whether vegetation indices and canopy temperature are representative of soil moisture at several crop growth stages. Findings from this study indicate that Red Edge Normalized Difference Vegetation Index could quantify variability of soil moisture tension at V6 (six leaf) (r2 = 0.850, p = 0.009) and V9 (nine leaf) (r2 = 0.913, p = 0.003) crop growth stages. Results suggest that satellite-derived vegetation indices may be useful for creating time-sensitive characterizations of soil moisture variability at large field-scales. When integrated with a stress threshold, synchronous canopy temperature was able to quantify soil moisture tension with some success during the reproductive crop growth stages. Further study is necessary to investigate additional crop growth stages, more crops, and other sources of multispectral imagery. Future studies are also needed to evaluate field-scale yield implications of variable rate irrigation management.